A heather attachment to HZG-4 X-ray diffractometer - Beneš, Ludvík (Univerzita Pardubice, 1996)
A simple and inexpensive heater attachment to the HZG-4 X-ray diffractometer, which can be used for investigation of thermal behavior of solids between 20 and 300 °C, is described. Using of this attachment is documented on a study of dehydration of [Mn(H2O)]0.25(VO)0.75PO4∙2H2O and intercalation of ethanol into VOPO4.